(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In 2018, I took part in the creative process of the theater play Nós Outros, developed by Fala Companhia de Teatro, created in relation to an experience of the cast and playwright and theater director Don Correa with indigenous people of the Guarani and Kaingang ethnic groups, in the Tupã Nhe’e Kretã Village, in Morretes, Paraná. In this article, I aimed to integrate Correa’s memories of the creative process with anthropological insights. This way I seek to interpretate scenic and dramaturgical procedures proposed by the director of the play inspired by amerindian perspectivism (Viveiros de Castro, 1996) and by anthropological art (Ingold, 2020). The article present border crossings made by the dramaturg as ethnographer and by the anthropologist as spectator, critic and as guest of the creative process undertaken by the cast. It underlines common features among dramaturgical and anthropological writings, presenting them as creative and authorial modes of relation with alterities.